501 Immunometabolism responses to disease in pigs and its impact on feed efficiency. (7th December 2018) - Gabler, N; Helm, E; DeMille, C; Curry, S; Schweer, W; Lonergan, S; Loving, C; Schwartz, K; Burrough, E
Abstract: Feed efficiency is simply defined as the ratio between growth and feed intake. However, defining the integration of genetic and environmental factors that alter molecular and physiological aspects of growth, appetite, or a combination thereof is quite complex and remains elusive. In livestock such as pigs, limited resources (i.e. nutrients and energy) to allocate towards maintenance, growth, and other life processes, and to what functions these resources are allocated dictates efficiency of feed utilization during both sickness and health. An important aspect of resource reallocation during inflammation or pathogen challenges is the metabolic flexibility of cells and tissues that allows for the immunometabolic prioritization of nutrients and energy for the immune response. It is expected that livestock, such as pigs, will be subjected to moderate and severe inflammatory or pathogen insults at some stage in their production life. However, overzealous or prolonged activation of the immune response will diminish skeletal muscle hypertrophy and whole body growth, and combined with reductions in feed intake, decreased feed efficiency often occurs. Appetite, intestinal function and integrity, skeletal muscle growth, and maintenance energy requirements can be altered in pigs encountering enteric and respiratory viruses including Porcine Reproductive and Respiratory Syndrome virus, Porcine Epidemic Diarrhea virus, and bacteria such as Mycoplasma hyopneumoniae, Lawsonia intracellularis, Salmonella Typhimurium, and Brachyspira hyodysenteriae. However, the severity of impact of these pathogens on performance parameters is dependent on the age of the pig, pathogen virulence, duration of infection, or co-infection with other agents. Further, these pathogen insults are year-round, increase days to reach market weight, and have a significant impact on economic returns for producers. This invited paper will discuss the molecular and physiological impact that inflammation and pathogen challenges have on feed efficiency in growing pigs as it relates to appetite, intestinal function and integrity, metabolism, and tissue accretion.